Conflict Management Strategies: A Case Study of Sharing Family Inheritance - Einsbie Grata Myn; Ahmad Yani (Formosa Journal of Applied Sciences, 2023)
Lack of recognising conflict management in the family environment in the division of inheritance property so as to cause quarrels and hostilities between families This study aims to provide a description of the case of the division of inheritance property. The type of research used is descriptive qualitative with a case study method. The results showed that some subjects had not fully implemented the appropriate conflict management process.